PERENCANAAN DAN METODE PELAKSANAAN PEKERJAAN PONDASI BORED PILE - Saputra, Parada Afkiki Eko (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2023)
Carrying out work on a building project includes data collection, research/investigation, feasibility studies, planning stage, design stage, procurement/tendering stage, construction implementation stage in the field, maintenance stage up to the preparation stage for building use. These elements work according to a predetermined working relationship pattern. The most important part of all activities is implementation activities. Implementation is the realization of the planning and design stages. Due to the different conditions between planning and implementation, flexibility or thoroughness is required in handling this implementation stage. Sensitivity in capturing and predicting all possibilities based on experience will greatly determine the contractor's success in completing the work. From all the foundation work in this project, it turns out that it does not apply theories rigidly, but can be carried out by considering other factors that do not make it possible to carry out work that is the same as the existing theory. These factors include the ability of the workforce including professionalism and work mentality, imperfect quality and condition of materials, unpredictable weather conditions, as well as difficulties faced in each job caused by imperfect designs and drawing plans. During project implementation, several deviations sometimes occur which can sometimes have fatal consequences for the safety of both workers (not wearing helmets when working) and future building users (work implementation is not according to plans approved by the supervisor). Deviations in foundation work that sometimes occur or negligence made by workers in carrying out work can cause the work results achieved to be not as expected.